HGF Stimulation of Rac1 Signaling Enhances Pharmacological Correction of the Most Prevalent Cystic Fibrosis Mutant F508del-CFTR - Moniz, Sónia (2012)
Cystic fibrosis (CF), a major life-limiting genetic disease leading to severe respiratory symptoms, is caused by mutations in CF transmembrane conductance regulator (CFTR), a chloride (Cl(-)) channel expressed at the apical membrane of epithelial cells. Absence of functional CFTR from the surface of respiratory cells reduces mucociliary clearance, promoting airways obstruction, chronic infection, and ultimately lung failure. The most frequent mutation, F508del, causes the channel to misfold, triggering its premature degradation and preventing it from reaching the cell surface. Recently, novel small-molecule correctors rescuing plasma membrane localization of F508del-CFTR underwent clinical trials but with limited success. Plausibly, this may be due to the mutant intrinsic plasma membrane (PM) instability. Herein, we show that restoration of F508del-CFTR PM localization by correctors can be dramatically improved through a novel pathway involving stimulation of signaling by the endogenous small GTPase Rac1 via hepatocyte growth factor (HGF). We first show that CFTR anchors to apical actin cytoskeleton (via Ezrin) upon activation of Rac1 signaling through PIP5K and Arp2/3. We then found that such anchoring retains pharmacologically rescued F508del-CFTR at the cell surface, boosting functional restoration by correctors up to 30% of wild-type channel levels in human airway epithelial cells. Our findings reveal that surface anchoring and retention is a major target pathway for CF pharmacotherapy, namely, to achieve maximal restoration of F508del-CFTR in patients in combination with correctors. Moreover, this approach may also translate to other disorders caused by trafficking-deficient surface proteins.